Anti-Bullying Strategy towards Parents: A Comparative Analysis between Principals of Experimental and Non-Experimental Primary Schools in Greece - Anastasiou, Adamos; Androutsou, Despoina; Valkanos, Efthymios; Stachtiaris, Georgios; Tsampos, Evangelos (Innovare Journal of Education, 2023)
School bullying is a type of bullying that occurs in an educational setting. In the present study, we examine the differences in strategy towards parents followed by principals of public experimental and non-experimental primary schools in Greece in their effort to deal with bullying regarding issues related to the proper treatment of the phenomenon. A sample of 11 school principals was the focus of this research. In particular, the population examined were the principals of the three public experimental primary schools of the prefecture of Thessaloniki and eight randomly selected principals of non-experimental public primary schools of the same prefecture. In the prefecture of Thessaloniki, the problem of bullying seems to exist and concern to a great extent the principals of primary education who constitute the sample of this research and pursue their strategy to find appropriate solutions for its immediate and effective coping. At the same time, these principals follow, to a significant degree, common practices in dealing with the phenomenon in their effort to reduce it or even eliminate it, revealing however significant shortcomings on their part.